PENGARUH KUALITAS PELAYANAN PEMBAYARAN E-SAMSAT TERHADAP KEPUASAN WAJIB PAJAK KENDARAAN BERMOTOR (Studi Kasus pada Kantor Samsat Kabupaten Banyuwangi) - Irianto, Dicky Fahmi; Wilujeng, Sri; Imaniar, Dimas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2024)
Effect Of E-Samsat Payment Service Quality On Motor Vehicle Taxpayer Satisfaction At The Samsat Office, Banyuwangi Regency. The e-Samsat payment service is no stranger to big cities, especially East Java. With e-Samsat services, people no longer need to queue to pay taxes, they can just pay at home without leaving the house. Samsat Banyuwangi is one of the offices that is successful in implementing an online payment system, this is an effort to improve services to taxpayers with fast and convenient service on an ongoing basis. E-Samsat is one proof of increasing motor vehicle tax payment services. The importance of analyzing data in research is to know clearly about the empirical relationship between the two variables studied. The analytical tool used by the researcher is quantitative data analysis, which is a structured report form which is stated with numbers, formulas that can be proven and tested for truth. The data collection method used in this research is using a questionnaire or questionnaire. The results of this study are the influence of service quality (X) on motor vehicle taxpayer satisfaction (Y). based on the results of empirical testing of the hypothesis by using product moment statistics, it produces a number of 0.214 which when compared to the critical price r table product moment for N = 96 with a significance level of 95%, the critical price for N = 95 with a significance level of 95%. The working hypothesis (Hi) is accepted, the null hypothesis (Ho) is rejected.